2022
DOI: 10.23887/jear.v5i4.43652
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Model Pembelajaran Mind Mapping dalam Meningkatkan Hasil Belajar Siswa di Sekolah Dasar

Abstract: Penyusunan pembelajaran yang kurang menarik bagi siswa, sehingga siswa cepat bosan dan kurang aktif dalam pembelajaran. Hal ini mengakibatkan hasil belajar siswa menjadi rendah. Tujuan penelitian ini adalah untuk menganalisis besarnya pengaruh model pembelajaran mind mapping dalam meningkatkan hasil belajar siswa sekolah dasar secara keseluruhan dan besar pengaruh model pembelajaran mind mapping dalam meningkatkan hasil belajar siswa sekolah dasar berdasarkan mata pelajaran. Metode yang digunakan dalam penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…This finding is reinforced by the findings of previous studies stating that the mind mapping model applied to student learning is proven to be able to influence student learning outcomes (R. B. Rahmawati et al, 2023;Safrizal et al, 2023;Wati, 2022). Microsoft Sway can increase student activity (Mawarni et al, 2022).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This finding is reinforced by the findings of previous studies stating that the mind mapping model applied to student learning is proven to be able to influence student learning outcomes (R. B. Rahmawati et al, 2023;Safrizal et al, 2023;Wati, 2022). Microsoft Sway can increase student activity (Mawarni et al, 2022).…”
Section: Discussionmentioning
confidence: 70%
“…Previous research findings stated that Sway-based learning media could foster a more conducive and meaningful learning environment to increase students' enthusiasm (Kurniasih, 2019;Widiastusi et al, 2019). The Minp Mapping model can encourage students to take an active role in their education because it places a student-centered emphasis on learning (Erwanda et al, 2022;Safrizal et al, 2023;Wati, 2022). Using Microsoft Sway in learning can improve student learning outcomes (Markamah & Nugraheni, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The application of this mind mapping learning model is also carried out on various variables such as motivation, interest in learning, learning achievement, critical thinking skills, learning outcomes and other variables (Kara & Liru, 2021). Based on the results of a literature review conducted by (Wati, 2022) that the mind mapping learning model in improving learning outcomes, while testing the magnitude of the influence of the mind mapping learning model in improving student learning outcomes in schools is in the medium, feasible category, so that educators who have never implemented the model Mind mapping learning can be tried in learning. Various studies reveal that the main mapping method shows significant things in increasing knowledge, skills, motivation and students.…”
Section: Introductionmentioning
confidence: 99%
“…Buzan (2006) revealed that Mind Mapping could integrate and improve the ability of the brain to work in a person, namely when storing one's memory efficiently. According to Wati (2022), the Mind Mapping learning model is a model that focuses on optimizing the work of the brain. The left and right hemispheres are used simultaneously to make knowledge formation work comprehensive and meaningful.…”
Section: Introductionmentioning
confidence: 99%